Heart failure as a risk factor of adverse drug reactions. Part 2: potential changes in pharmacokinetics of some drugs - A. P. Pereverzev; O. D. Ostroumova (Izdatelstvo OKI, 2022)
Drug administration, can be potentially associated with adverse drug reactions (ARDs), including serious ones, contributing to an increase in the risk of death or the development of conditions that potentially increase mortality and / or morbidity and / or become the cause of clinical manifestations, requiring the patient to seek medical attention or hospitalization - so called drug-induced diseases (DID). Some pathological conditions, like chronic heart failure (CHF), are potential risk factors for DID due to changes in the pharmacokinetics and pharmacodynamics of drugs. For example, after oral administration of fosinopril, the average T1/2 value in patients with CHF II - III NYHA functional class was 14.2 (±7.3) hours, and in healthy individuals of the control group - 11.0 (±5.2) hours. Values of AUC per os and Cmax were also slightly higher in patients with heart failure (HF) than in healthy individuals, and Cl per os, on the contrary, were lower. After intravenous administration of fosinopril, similar results were observed. Another example is the altered absorption of furosemide in patients with decompensated heart failure. Thus, in patients with heart failure, as the edema syndrome is corrected, the time to the onset of the maximum drug concentration in the blood serum (Tmax ) decreases by 27 % and Cmax increases by 29 %, which may indicate a decrease in the slowdown in the absorption rate (by 57 %). Since furosemide is mainly excreted in the urine unchanged, the observed changes in Cmax and Tmax could be associated with delayed gastric emptying, decreased intestinal motility, or edema of the intestinal wall. Individual selection of the dose and dosing regimen, taking into account the characteristics of the pharmacokinetics of drugs in patients with CHF, will help improve the quality of life and prevent potential ADR.